Lodge Farmhouse, Middle Road, Denton, Norfolk, Oxygen Isotope Dendrochronology of Oak Timbers - Neil Loader (Research Report Series 6-2021, 2021)
As part of an initiative to investigate the practical extent of the south-centralEngland chronology for isotopic dating, two timbers that had been securely datedby ring-width dendrochronology from Lodge Farmhouse, Denton were sampled foroxygen isotope analysis. Fifty measurements were obtained on latewood from singlegrowth-rings of core LFD-04 from a section of a west wall-plate (rings 0–49 of themeasured ring-width series which spans AD 1252–1335) and 96 measurementswere obtained on latewood from single growth-rings of core LFD-12 from thenorthernmost east principal post (rings 1–96 of the measured ring-width serieswhich spans AD 1225–1320).The two isotopic series cross-match when offset by 20 years. This is consistent withthe ring-width cross-matching. The 96-year isotopic mean cross-dates (t =6.15,1/p=105264, IF>1000) with the south-central England oxygen isotope masterchronology, at a position that is compatible with that provided by ring-widthdendrochronology. The isotopic series LFD-12 dates independently (t =6.15,1/p=103843, IF>1000), but the shorter LFD-04 does not date independently.The location of Lodge Farmhouse in East Anglia is in an area that can bechallenging for ring-width dendrochronology. It is also located well to the east of thesouth-central England master oxygen isotope chronology. This initial studysuggests that, at present, secure dating using oxygen isotope measurements may bepossible in this region, but may not routinely be obtained from short series ofisotopic measurements on single timbers. An oxygen isotope master chronology forEast Anglia may be required to enhance the potential for applying oxygen isotopedendrochronology in this region.